2017
DOI: 10.1080/16000870.2017.1299283
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric response of the Atlantic Meridional Ocean Circulation to freshwater anomalies in a strongly-eddying global ocean model

Abstract: The Atlantic Meridional Overturning Circulation (AMOC) responds sensitively to density changes in regions of deepwater formation. In this paper, we investigate the nonlinear response of the AMOC to large amplitude freshwater changes around Greenland using a strongly-eddying global ocean model. Due to a 0.5 Sv freshwater input, the maximum AMOC at 35 • N decreases by about 50% over a 45 year period. The AMOC does not recover over a period of 50 years when the freshwater input is ceased at year 45. However, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…S1) show realistic strength and location of the Gulf Stream and other subpolar boundary currents, taking into account the resolution of the model. Previous work using the same model in a similar set-up found a well-represented distribution of currents, kinetic energy and water-mass properties at basin scale (Maltrud et al, 2010;Weijer et al, 2012;Brunnabend and Dijkstra, 2017). Moreover the modelled mixed layer depth qualitatively matches the spatial pattern derived from ARGO floats (Våge et al, 2009;, where the areas of deepest convection are found in the south-west Labrador Sea, in the Greenland Sea and around the Iceland-Scotland Ridge.…”
Section: Model Data and General Performancesupporting
confidence: 73%
“…S1) show realistic strength and location of the Gulf Stream and other subpolar boundary currents, taking into account the resolution of the model. Previous work using the same model in a similar set-up found a well-represented distribution of currents, kinetic energy and water-mass properties at basin scale (Maltrud et al, 2010;Weijer et al, 2012;Brunnabend and Dijkstra, 2017). Moreover the modelled mixed layer depth qualitatively matches the spatial pattern derived from ARGO floats (Våge et al, 2009;, where the areas of deepest convection are found in the south-west Labrador Sea, in the Greenland Sea and around the Iceland-Scotland Ridge.…”
Section: Model Data and General Performancesupporting
confidence: 73%
“…S1) show a realistic strength and location of the Gulf Stream and other subpolar boundary currents, taking into account the resolution of the model. Previous work using the same model in a similar setup found a well-represented distribution of currents, kinetic energy, and water-mass properties at basin scale (Maltrud et al, 2010;Weijer et al, 2012;Brunnabend and Dijkstra, 2017). Moreover, the modeled mixed layer depth qualitatively matches the spatial pattern derived from Argo floats (Våge et al, 2009;, whereby the areas of deepest convection are found in the southwest Labrador Sea, in the Greenland Sea, and around the Iceland-Scotland Ridge.…”
Section: Model Data and General Performancesupporting
confidence: 71%
“…The Atlantic Meridional Overturning Circulation (AMOC) is a fundamental component of the Earth's climate system (Lozier, 2012;Buckley and Marshall, 2016). Over the last few decades the traditional view of an ocean conveyor with an upper poleward current transporting warm waters to higher latitudes, and a downward branch with intermediate and deeper denser waters that originate in the regions of deep convection and move toward the Equator (Broecker, 1987(Broecker, , 1991, has been revised.…”
Section: Introductionmentioning
confidence: 99%
“…The question of whether the AMOC can recover following a climate change-induced collapse has been addressed in a number of previous "hosing" experiments using climate models, in which a large amount of freshwater is artificially fluxed into the North Atlantic over a finite period of time (e.g., Brunnabend & Dijkstra, 2017;den Toom et al, 2014;Jackson & Vellinga, 2013;Liu et al, 2017;Mignot et al, 2007;Vellinga & Wood, 2008;Wood et al, 2003;Zhang & Delworth, 2005). Here, however, we instead address how the AMOC will respond on multidecadal timescales to a high-latitude freshwater flux (FWF) that is both modest enough to retain an active AMOC and sustained continuously in time.…”
Section: Introductionmentioning
confidence: 99%